Association between endodontic treatment quality and apical periodontitis assessed through cone beam computarized tomography in a colombian population - Blanco-Fuentes, Bibiana Yorley; Moreno-Monsalve, Jaime Omar; Mesa-Herrera, Uriel (Universidad y Salud, 2023)
Introduction: The prevalence of apical periodontitis in teeth with endodontic treatment ranges between 35% and 60%, and a strong association has been found with respect to high levels of systemic inflammation markers (pro-inflammatory cytokines, protein C-reactive and interleukin 6) caused by apical periodontitis. Studies have shown that an adequate endodontic treatment can reduce C-reactive protein levels in healthy individuals and those with apical periodontitis. Objective: To evaluate the frequency of apical periodontitis in a selected Colombian adult population and its correlation with the quality of endodontic treatment. Materials and methods: Observational, analytical, cross-sectional study. The frequency of apical periodontitis was determined in 318 CBCTs of patients from Bucaramanga and Medellin, and the association between quality of endodontic treatment and periapical status was analyzed. Results: Only 37.66% of the observed teeth were considered healthy, whereas 44.81% were classified as teeth with appropriate endodontic treatment. Quality of endodontic treatment significantly affected the condition of the apical periodontium. Conclusions: The analyzed treatments had a high apical periodontitis frequency, which was associated with a high frequency of inadequate endodontic treatments.